Phase formation and surface morphology of nickel doped Ba1-xSrxTiO3 ceramics prepared by sol-gel technique - Deepthi, K.A.; Balachandran, R.; Ong, B.H.; Wong, H.Y.; Tan, K.B.; Yow, H.K.; Daud, Z.B.M. (Maney Publishing, 2014)
Varied compositions in the barium strontium titanate ternary system were prepared through the slow injection sol-gel technique. Nickel dopant was introduced through a general formula of Ba1-xSrxTi1-yNiyO3 (x = 0.4 and 0.5; y = 0.1 and 0.4 mol-%). Thermogravimetric analysis revealed that barium strontium titanate gels were completely dried and stabilised at 1000 degrees C. All barium strontium titanate samples were confirmed as phase pure perovskite by qualitative X-ray diffraction analysis in which Nickel-doped subsolidus solution was formed successfully after calcinations at 1000 degrees C. On the other hand, there was a sign of agglomeration discernible in the prepared BST samples and the grain sizes were found to be in the range of 39.66-71.87 nm.